2002
DOI: 10.1101/gr.62002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Heterogeneity at the 3′ Ends of Human mRNAs

Abstract: The publication of a draft of the human genome and of large collections of transcribed sequences has made it possible to study the complex relationship between the transcriptome and the genome. In the work presented here, we have focused on mapping mRNA 3Ј ends onto the genome by use of the raw data generated by the expressed sequence tag (EST) sequencing projects. We find that at least half of the human genes encode multiple transcripts whose polyadenylation is driven by multiple signals. The corresponding tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 22 publications
3
45
1
Order By: Relevance
“…Bioinformatic studies indicate that cleavage site choice within a poly(A) site is inherently imprecise (Pauws et al 2001;Tian et al 2005). In addition to cleavage site heterogeneity, alternative selection among different poly(A) sites (that range over distances in the kilobase range) is observed within the majority of human pre-mRNAs (Iseli et al 2002;Tian et al 2005). The consequences of alternative poly(A) site choice may impact the protein coding capacity of the message, as well as its localization, translation efficiency, and stability (Edwalds-Gilbert et al 1997).…”
Section: A Need For Precision and Uniformitymentioning
confidence: 99%
“…Bioinformatic studies indicate that cleavage site choice within a poly(A) site is inherently imprecise (Pauws et al 2001;Tian et al 2005). In addition to cleavage site heterogeneity, alternative selection among different poly(A) sites (that range over distances in the kilobase range) is observed within the majority of human pre-mRNAs (Iseli et al 2002;Tian et al 2005). The consequences of alternative poly(A) site choice may impact the protein coding capacity of the message, as well as its localization, translation efficiency, and stability (Edwalds-Gilbert et al 1997).…”
Section: A Need For Precision and Uniformitymentioning
confidence: 99%
“…This proportion is identical to the observed frequency in human annotated mRNAs (Gautheret et al 1998). By EST analysis, alternative polyadenylation seems to occur in at least 29%-40% of genes (Gautheret et al 1998;Beaudoing et al 2000), and many more such variable polyadenylation events probably escape the analysis, due to long-range heterogeneity of the 3Ј ends (Iseli et al 2002).…”
Section: Classes Of Polyadenylation Sitesmentioning
confidence: 99%
“…For quality control, we did not consider the completeness of the UTR regions, because variability of the starting site (Suzuki et al 2001a,b), 5∼50 bp trimming of 5Ј ends in the reference cDNA clones generated by conventional methods (Gubler and Hoffman 1983) and variation of polyadenylation sites (Beaudoing et al 2000;Iseli et al 2002), which also suggest that public databases probably do not contain all of the existing full-length UTR variations.…”
Section: Gene Discovery By Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNP present in the 3Ј flanking region (C1801G) falls outside the putative transcribed region, and the current gene annotation suggests it would not be present in the mRNA sequence where it could potentially influence mRNA transport and stability, a well-documented phenomenon. However a recent study (28) revealed that up to 50% of currently annotated genes use more distant polyadenylation signals with varying efficiencies that were not necessarily dependent on distance from the open reading frame. It is therefore possible that the use of an alternate polyadenylation signal further downstream would include the 3Ј flanking SNP in the mRNA strand, presenting a potential mechanism for the variant to influence mRNA transport and stability.…”
Section: Discussionmentioning
confidence: 99%